Alkaline phosphatase–streptavidin conjugate (APSA) enzyme and binding activity over time and storage conditions - Nan Cheng; Lloyd Johnson; Jaimie Dufresne; Sina Mazinani; John G. Marshall (Biochemistry and Biophysics Reports, 2025)
Alkaline phosphatase (AP) linked to streptavidin (SA) in the form of the APSA enzyme conjugate is required for diagnostic screening for a variety of clinical conditions world wide. The enzyme activity of APSA conjugates in the liquid phase showed variation across samples that declined with storage time. Random sampling of the enzyme activity in the liquid phase (ANOVA p < 2E-16; Regression p < 0.043) and the binding plus enzyme activity of APSA in the model assay (R2 > 0.99) of biotinylated human IgG (B-h-IgG) directly adsorbed to 96 well plates showed a similar loss of function over time (ANOVA p < 9.15E-15, Regression p <1.1E-9). The enzyme AP showed little dissociation from the SA moiety while proteolysis of the BSA carrier was observed. Covalent protease inhibitors 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride (AEBSF) or tosyl-l-lysine chloromethyl ketone hydrochloride (TLCK) abrogated AP enzyme activity, but the competitive inhibitors epsilon-aminocaproic acid (EACA) and benzamidine (BNZ) had no protective effect on APSA activity over time. Samples of APSA showed large variation in enzyme activity (p ≤ 2E-16) and so were titrated by the colorimetric assay and standardized against indigo blue in DMSO to achieve an initial OD value of ∼1.0 at 595 nm prior to following activity over storage time. After titration, the effect of temperature, addition of glycerol prior to freezing, and freeze drying with or without trehalose and sucrose, on alkaline phosphatase activity was compared using a sampling schedule over storage time. The alkaline phosphate activity was not immediately sensitive to freeze-drying but was sensitive to storage time and ultra-low temperatures, but the addition of sugars or glycerol to the APSA prevented some of the activity loss. Storage of APSA on wet ice or in 50 % glycerol at −20 °C retained about 50 % of the starting optical density reading of APSA after 170 days in storage.